The Impact of Deferred Mining Exploration and Development Costs on PT United Tractors Tbk’s Net Income for The Current Year - Alya Syifa Rahman; Naomi Arthaprillia Purba; Elizabeth Tiur Manurung (Devotion : Journal of Research and Community Service, 2026)
The mining industry is one of the strategic sectors in the Indonesian economy, but its capital-intensive characteristics cause operational costs, especially mining exploration and development costs, to greatly determine the company's financial performance. This study aims to analyze the correlation between exploration costs and mining operating expenses on the net profit of PT United Tractors Tbk for 25 years, using annual financial statement data for the period 2000 - 2025, as well as looking at how PT United Tractors Tbk developed from a heavy equipment distributor to a mining contractor and as a mining concession owner from 2020-2025. The research method used was a quantitative approach with simple linear regression analysis, using secondary data from the company's annual financial statements. The results of the study show that the deferred mining exploration and development costs have a significant effect on net profit, any increase in mining costs will increase net profit. It can be concluded that the efficient management of mine operating costs is essential to maintain profitability. Therefore, companies are advised to continue to evaluate and optimize costs to remain competitive amid fluctuations in the commodity market.